Dutch guidelines for interventional cardiology: institutional and operator competence and requirements for training - Aengevaeren, W.R.M. (2005)
Interventional cardiology is an expanding field within cardiovascular medicine and today it is generally accepted that cardiologists require specific training, knowledge and skills. Hospitals where coronary interventions are performed must be properly equipped and able to provide specialised care. Percutaneous coronary interventions are frequently used for coronary revascularisation. The public should have confidence in the uniformity of high quality care. Therefore, such quality of care should be maintained by certification of the individual operators, general guidelines for institutional requirements and formal audits. The Netherlands Society of Cardiology (NVVC) will be implementing a new registration system for cardiologists with a subspecialisation that will include registration for interventional cardiology. The NVVC asked the Working Group of Interventional Cardiology (WIC) to update the 1994 Dutch guidelines on operator and institutional competence, and requirements for training in interventional cardiology in order to incorporate them into the official directives. The present guidelines represent the expert opinion of the Dutch interventional cardiology community and are in accordance with international regulations. After two rounds of discussion, the NVVC approved the guidelines in November 2004 during the autumn meeting.